2015
DOI: 10.1007/s10815-015-0465-7
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis on human sperm tail: comparison between normozoospermia and asthenozoospermia

Abstract: Purpose Asthenozoospermia is a common cause of human male infertility characterized by reduced sperm motility. The molecular mechanism that impairs sperm motility is not fully understood. This study proposed to identify novel biomarkers by focusing on sperm tail proteomic analysis of asthenozoospermic patients. Methods Sperm were isolated from normozoospermic and asthenozoospermic semen samples. Tail fractions were obtained by sonication followed by Percoll gradient. The proteins were extracted by solubilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“…Zalata et al (2012) showed that it correlated negatively with, inter alia, sperm count, motility, linear velocity, and significantly correlated positively with the percentage of abnormal forms of spermatozoa and sperm DNA fragmentation. Hashemitabar, Sabbagh, Orazizadeh, Ghadiri, and Bahmanzadeh (2015) compared the concentration of sperm tail proteins in normozoospermic and astenozoospermic men. The experiment showed increased levels of 14 proteins in astenozoospermic patients, CLU among them.…”
Section: Clu Concentration In Seminal Plasmamentioning
confidence: 99%
“…Zalata et al (2012) showed that it correlated negatively with, inter alia, sperm count, motility, linear velocity, and significantly correlated positively with the percentage of abnormal forms of spermatozoa and sperm DNA fragmentation. Hashemitabar, Sabbagh, Orazizadeh, Ghadiri, and Bahmanzadeh (2015) compared the concentration of sperm tail proteins in normozoospermic and astenozoospermic men. The experiment showed increased levels of 14 proteins in astenozoospermic patients, CLU among them.…”
Section: Clu Concentration In Seminal Plasmamentioning
confidence: 99%
“…It has been hypothesised that the sperm protein profile in infertile men is altered, and some researchers have assessed these profiles in several male infertility conditions including varicocele (Agarwal, Sharma, Samanta, Durairajanayagam, & Sabanegh, ; Agarwal, Sharma, Durairajanayagam, Ayaz, et al., ; Agarwal, Sharma, Durairajanayagam, et al., ; Hosseinifar et al., ), obesity (Kriegel et al., ; Liu et al., ), smoking (Chen et al., ), failed fertilisation after assisted reproduction techniques (ART; Frapsauce et al., ; Legare et al., ; Pixton et al., ), asthenozoospermia (Amaral et al., ; Hashemitabar, Sabbagh, Orazizadeh, Ghadiri, & Bahmanzadeh, ; Liu et al., ; Martinez‐Heredia, de Mateo, Vidal‐Taboada, Ballesca, & Oliva, ; Parte et al., ; Shen, Wang, Liang, & He, ; Siva et al., ; Zhao et al., ) and idiopathic infertility (Legare et al., ; McReynolds et al., ; Xu et al., ). Sperm protein profiles have also been evaluated in men with semen oxidative stress (Ayaz et al., ; Sharma et al., ) and sperm DNA fragmentation (Intasqui et al., ; de Mateo et al., ), which are common causes of male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…LOC103474644 (product ID: XP_008423986) on chromosome 2, showed higher expression ( p adj = .0008, LogFC = 0.95) in the LS than the HS line and it codifies for a keratin Type II cytoskeletal protein (KRT) which has been found to be upregulated in asthenozoospermic human males (Hashemitabar, Sabbagh, Orazizadeh, Ghadiri, & Bahmanzadeh, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Only three genes were significantly upregulated in the LS line but in all three cases, the fold change between selection lines was low. The most interesting of these genes was KRT, which has higher expression levels in asthenozoospermic human male patients than in normal sperm donors (Hashemitabar et al, 2015). In humans, it seems that the higher expression of KRT in asthenozoospermia is a compensatory effect on lower levels of tyrosine phosphorylation (Hashemitabar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation